Scientific engineering education: convergence of the russian and german experience - V. . Gorokhov (Высшее образование в России)
Since the New Time the precondition for the technological modernization of the modern society has been being the organization of the scientific engineering education. In this articleit is shown on some historical examples that this is also very important indicator of thescientific and technological development.